1999
DOI: 10.1021/la981104e
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Forces between E. coli Bacteria and Biomaterial Surfaces

Abstract: Bacterial infection of biomaterial surfaces is an important problem in the biomedical and health industries. The design of materials resistant to infections necessitates an understanding of the forces driving bacterial adhesion. Escherichia coli cells were immobilized onto the tip of a standard atomic force microscope (AFM) cantilever, and force measurements were performed by approaching the modified cantilever onto mica, hydrophilic glass, hydrophobic glass, polystyrene, and Teflon. Consistent with prior qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
324
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(358 citation statements)
references
References 33 publications
25
324
9
Order By: Relevance
“…The acid-base theory also has been applied to the adhesion between cells and biological materials [386], to the adhesion between blood proteins and several functional groups [362].…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 99%
See 1 more Smart Citation
“…The acid-base theory also has been applied to the adhesion between cells and biological materials [386], to the adhesion between blood proteins and several functional groups [362].…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 99%
“…First attempts in this direction were made by Razatos et al [980] who demonstrated that it is possible to coat silicon nitride AFM cantilevers including the tip with a layer of E. coli cells, if the cells were fixed by glutaraldehyde treatment. The authors took advantage of such functionalized tips to study the adhesion of E. coli [386,981] (see also Ref. [982]).…”
Section: Cell Probe Measurementsmentioning
confidence: 99%
“…Bacteria often adhere to surfaces and form biological communities called biofilms [1] that develop in almost all types of biomedical devices [2]. These sessile cells are typically more resistant to antimicrobial agents than planktonic ones, have a decreased susceptibility to host defense systems and function as a source of resistant microorganisms responsible for many hospital acquired infections [3].…”
Section: Introductionmentioning
confidence: 99%
“…These sessile cells are typically more resistant to antimicrobial agents than planktonic ones, have a decreased susceptibility to host defense systems and function as a source of resistant microorganisms responsible for many hospital acquired infections [3]. Moreover, biofilm spreading on the surface upon prolonged use of the biomedical device can cause material biodegradation, changes in surface properties and deterioration of the medical functionality [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, attractive interactions have been observed, such as with Candida parapsilosis and glass, 36 with Bacillus mycoides spores and hydrophobically treated glass, 55 and glutaraldehyde-treated E. coli cells interacting with mica, glass, Teflon, or polystyrene. 56 The sources of the attractions are believed to be specific interactions between microbial macromolecules and the interacting substrate. Although such interactions would hypothetically be present in all cases, often steric repulsion is so large that it masks all such specific interactions.…”
Section: Discussionmentioning
confidence: 99%